Henchir Bourgou (Djerba), Tunesien. Die Arbeiten der Jahre 2017 bis 2019 - Ben Taher , Sami; von Rummel, Philipp; Ritter, Stefan; Aoudi, Mekki; Dinies , Michèle; Fassbinder , Jörg; Mansel, Karin; Möller, Heike; Mukai, Tomoo; Peters, Joris; Reichmuth, Silvio; Trixl, Simon (e-Forschungsberichte des DAI, 2020)
The ancient site of Henchir Bourgou (Djerba), Tunisia, is the object of archaeological research conducted jointly by the Tunisian National Heritage Institute, the Ludwigs Maximilians University Munich and the German Archaeological Institute since 2017. The reports presents an overview on the activities in Henchir Bourgou done in 2017–2019 and gives an outlook on the potential of the site with its stratigraphy covering more than thousand years of settlement history.